2023
DOI: 10.1021/acs.est.3c04843
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Low-Cost PM2.5Sensors in Mobile Settings

Priyanka deSouza,
An Wang,
Yuki Machida
et al.

Abstract: Low-cost sensors (LCSs) for measuring air pollution are increasingly being deployed in mobile applications, but questions concerning the quality of the measurements remain unanswered. For example, what is the best way to correct LCS data in a mobile setting? Which factors most significantly contribute to differences between mobile LCS data and those of higher-quality instruments? Can data from LCSs be used to identify hotspots and generate generalizable pollutant concentration maps? To help address these ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Results from static testing and calibration of LCS colocated with reference stations will also not necessarily transfer to mobile monitoring. It has been shown that calibration models, particularly complex models that are well fitted to a specific environment, are often not transferable between different locations. , Moreover, mobile use introduces additional factors such as vibration of the nodes, high and variable wind speeds, interference from vehicular pollution, rapid changes in concentrations and environmental factors, and nonisokinetic sampling of particles. Depending on the type of sampling, the inlet orientation, relative to the direction of movement, may affect the sample flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Results from static testing and calibration of LCS colocated with reference stations will also not necessarily transfer to mobile monitoring. It has been shown that calibration models, particularly complex models that are well fitted to a specific environment, are often not transferable between different locations. , Moreover, mobile use introduces additional factors such as vibration of the nodes, high and variable wind speeds, interference from vehicular pollution, rapid changes in concentrations and environmental factors, and nonisokinetic sampling of particles. Depending on the type of sampling, the inlet orientation, relative to the direction of movement, may affect the sample flow rate.…”
Section: Introductionmentioning
confidence: 99%